Discordance Between Radiologic Findings and Molecular Testing in Patients With Underlying Hematologic Malignancy and Coronavirus Disease 2019. (22nd September 2020) - Raja, Mohammed; Natori, Yoichiro; Chandorkar, Aditya; Camargo, Jose F; Simkins, Jacques; Andrews, David; Bradley, Terrence; Watts, Justin; Komanduri, Krishna; Morris, Michele I; Fishman, Joel E
Abstract: Severe acute respiratory syndrome coronavirus 2 is associated with severe disease in patients with hematologic malignancy. We report a series of patients with underlying hematologic malignancy and coronavirus disease of 2019 with discrepancy between radiographic findings and molecular testing. Initial chest x-ray findings should raise suspicion in immunosuppressed patients with typical clinical presentation even with negative initial testing.